A Managerial Approach in Resource Allocation Models: An Application in US and Canadian Oil and Gas Companies - Mohamadinejad, Hengameh; Amirteimoori, Alireza; Kordrostami, Sohrab; Hosseinzadeh Lotfi, Farhad (Yugoslav Journal of Operations Research; Vol 33 No 3 (2023)DO - 10.2298/YJOR221016004M, 2023)
In resource allocation and target setting problems, a central decision makers’ managerial standpoint has a pivotal role, especially when we encounter undesirable outputs such as the greenhouse gas (GHG) emissions. In such circumstances, firms have to cooperate with each other, to achieve the central planner’s aims. Looking into literature reveals that the existing resource allocation models based on data envelopment analysis (DEA) have not aptly considered the influence of managerial efforts and technological innovations in this sense. This study proposes a centralized model incorporating managerial disposability. This model not only reflects the leadership performance of the central planner and the technological novelty perspective in the resource allocation and target setting problem, but also has a positive modification against an environmental adaptation change. In order to illustrate the applicability of our resource allocation and target setting model, a case study of 23 US and Canadian oil and gas companies has been conducted. Analysis of the results reveals the appropriacy and efficiency of our proposed model in dealing with the current perspectives concerning the issue of resource allocation and target setting.